Die karakterisering van Pilatus in die Johannesevangelie - Tolmie, DF (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The characterisation of Pilate in the Gospel of John Quite a number of scholars have already investigated the characterisation of Pilate in the Fourth Gospel, but no agreement has thus far been reached on how this interesting character should be interpreted. In this article an overview of some of the interpretations of the characterisation of Pilate is presented before an own analysisis attempted. This is done in terms of the approach to characterisation proposed by Seymour Chatman, according to which characters in narrative texts may be studied from the perspective of the traits which are revealed to the implied reader as the narrative unfolds. In this article the paradigm of traits associated with Pilate is discussed and it is shown how the characterisation of Pilate develops as the narrative unfolds.